Characterization of Recessive Parkinson Disease in a Large Multicenter Study. Issue 4 (28th July 2020) - Lesage, Suzanne; Lunati, Ariane; Houot, Marion; Romdhan, Sawssan Ben; Clot, Fabienne; Tesson, Christelle; Mangone, Graziella; Toullec, Benjamin Le; Courtin, Thomas; Larcher, Kathy; Benmahdjoub, Mustapha; Arezki, Mohamed; et al.
Abstract : Studies of the phenotype and population distribution of rare genetic forms of parkinsonism are required, now that gene‐targeting approaches for Parkinson disease have reached the clinical trial stage. We evaluated the frequencies of PRKN, PINK1, and DJ‐1 mutations in a cohort of 1, 587 cases. Mutations were found in 14.1% of patients; 27.6% were familial and 8% were isolated. PRKN was the gene most frequently mutated in Caucasians, whereas PINK1 mutations predominated in Arab‐Berber individuals. Patients with PRKN mutations had an earlier age at onset, and less asymmetry, levodopa‐induced motor complications, dysautonomia, and dementia than those without mutations. ANN NEUROL 2020;88:843–850